Reading, democracy and discipline: Premises for reading activities in Swedish primary schools from 1967 to 1969 - Dolatkhah, M.; Lundh, A.H. (University of Tartu Press, 2014)
In Sweden, as well as in many other countries, children’s literacy is a much debated topic. In the public discourse, politicians, researchers, and other groups are discussing the reading abilities, reading habits, and changing media preferences of children and youth. These discussions encompass several different lines of thought, but perceived problems with computers, digital media, and document technologies are often at the heart of the debate. For example, the computerisation of children’s home environments has been interpreted as one of the major causes for the decline in traditional reading interests and reading skills among children and youth (Rosén 2012). It has also been argued that theheavy use of digital media actually restructures the human brain and makes it more suited to superfi cial skimming and scanning than the in-depth concentrated reading associated with traditional printed books (Carr 2010). Some studies have found that educators and librarians associate printed books with good childhoods, and digital media technologies are thought to endanger the childhoods of contemporary children (Lundh, Davidsson & Limberg 2011).In these discussions, many different values are attributed to book reading. Some relate to cognition, such as creative imagination, concentration, as well as linear, abstract, and complex thinking. Other values are social, such as the idea of book reading being a part of a good childhood. In the Swedish debate, researchers and politicians also connect the reading of literature to the democratic capital of the society. It is seen as a practice by which the citizens access the information they need and by which they can develop and mature as potential political actors (Government Bill 2013/14:3; Persson 2007).In summary, it can be said that the contemporary discussions of reading often centre on an experience of transition from one culture or practice of reading to another, and on the role played by new media technologies in this process. We argue that in order to understand this transition – and the experience of it – it is important to explore not only the most recent developments and the use of new media technologies today. It is also important to criticallyscrutinise historical evidence of the culture of reading that we are now said to be leaving behind, and thus avoid taking it for granted.This article is one of the fi rst steps in a larger research project, Reading, traditions and negotiations: Reading activities in Swedish classrooms 1967–1969, which is an examination of how reading as an activity was shaped in Swedish primary schools in the late 1960s. The primary data for this project consist of a large number of video and sound recordings from Swedish primary school classrooms between 1967 and 1969. By analysing this material, we hope to contribute to the understanding of changing reading habits by investigating an important part of Swedish reading culture as it developed in the decades after World War II, namely the reading practices taught in the schools. The publicschool system was one of the most important cornerstones in the building of a reading culture in post-war Sweden, and it was also a product of particular historical and societal circumstances and ideologies.Since an important aspect of reading practices is the degree to which they are embedded in historical circumstances and institutions, a contextual understanding is required for the research project generally. Christine Pawley, who studies the history of reading, has drawn attention to organisations, both commercial and public, as foci for the research on reading practices (Pawley 2009).Organisations, she argues, represent a theoretical meso-level of analysis, where the interplay between macro-level structures and micro-level actions occurs. Pawley pays particular attention to structural categories such as gender, race and class. We assume that organisations can also mediate and manifest structural phenomena such as ideologies and discourses, and that they are places where individuals can negotiate, contest, adapt to, and contribute to such structures.During the decades after t he World War II, the Swedish educational system was thoroughly reformed. In 1962, a new curriculum instituted comprehensive and compulsory public schooling, which was intended to tackle certain social and political issues. In addition, the curriculum provided the school system with a normative conceptualisation of reading. Analytically, the institution of the new comprehensive and compulsory school system – and its curriculum – can be seen an important link between reading as an activity and broader societal circumstances. The intention of this paper is to lay a foundation for our further studies, by analysing the historical and institutional context in which school reading took place, with a particular focus on the curriculum and its conceptualisations of reading that was current at that time.